Synovial Chondromatosis of the Cervical Spine: A Case Report and Review of the Literature. (May 2014) - Shaw, Andrew; Zibly, Zion; Prasad, Vinay; Ikeda, Daniel; Boue, Daniel; Governale, Lance S.
Synovial chondromatosis is a benign condition characterized by metaplastic changes of the synovial membrane typically affecting large joints. Cervical spine involvement is rare and has not been reported in a teenager. The authors report a case of cervical synovial chondromatosis in a 19-year-old male presenting with left-sided weakness and numbness from spinal cord compression. After gross total resection was accomplished via laminoplasty, the patient's presenting symptoms improved and continued to do so over the follow-up period. The likely cause of the synovial chondromatosis in this patient was repetitive neck trauma as a child from a motor vehicle accident and football. This case demonstrates that the pathophysiology of this rare entity can initiate in the pediatric population. Although rare, synovial chondromatosis should be considered in the differential diagnosis of calcified extradural masses in the teenage population.